Transmembrane TNF drives osteoproliferative joint inflammation reminiscent of human spondyloarthritis - Kaaij, Merlijn H.; van Tok, Melissa N.; Blijdorp, Iris C.; Ambarus, Carmen A.; Stock, Michael; Pots, Désiree; Knaup, Véronique L.; Armaka, Marietta; Christodoulou-Vafeiadou, Eleni; van Melsen, Tessa K.; Masdar, Huriatul; Eskes, Harry J.P.P.; et al. (Journal of Experimental Medicine, 2020)
TNF plays a key role in immune-mediated inflammatory diseases including rheumatoid arthritis (RA) and spondyloarthritis (SpA). It remains incompletely understood how TNF can lead to different disease phenotypes such as destructive peripheral polysynovitis in RA versus axial and peripheral osteoproliferative inflammation in SpA. We observed a marked increase of transmembrane (tm) versus soluble (s) TNF in SpA versus RA together with a decrease in the enzymatic activity of ADAM17. In contrast with the destructive polysynovitis observed in classical TNF overexpression models, mice overexpressing tmTNF developed axial and peripheral joint disease with synovitis, enthesitis, and osteitis. Histological and radiological assessment evidenced marked endochondral new bone formation leading to joint ankylosis over time. SpA-like inflammation, but not osteoproliferation, was dependent on TNF-receptor I and mediated by stromal tmTNF overexpression. Collectively, these data indicate that TNF can drive distinct inflammatory pathologies. We propose that tmTNF is responsible for the key pathological features of SpA.
CRIS-Team Scopus Importer:2020-07-24